FRI0530 Efficacy and Tolerability of Pamidronate in Chronic Recurrent Multifocal Osteomyelitis. (10th June 2014) - Galeotti, C.; Loschi, S.; Adamsbaum, C.; Koné-Paut, I.
Abstract : Background: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare autoinflammatory disease in children. First-line treatments used are nonsteroidal anti-inflammatory drugs (NSAIDS). Secondary treatments after NSAIDS in case of refractory CRMO are not standardized and have been few evaluated. Biphosphonates, in particular pamidronate, have been used off label in a limited number of patients 1 . Objectives: A retrospective survey and chart review to evaluate the reasons for use, the efficacy and the tolerability of IV pamidronate in 13 patients with difficult CRMO. Methods: Thirteen of the 30 patients followed in the pediatric rheumatology unit at Bicêtre hospital, were analyzed retrospectively. Pamidronate treatment was documented as follows: reasons for its use, administration scheme, clinical efficacy (pain was evaluated by visual analog scale (VAS) and tolerability. Radiological changes were evaluated where available. Results: Thirteen patients (4M, 9F) were treated by pamidronate from November, 2004. The median age at treatment was 10 years (6-14 years). Pamidronate was administered, on demand, intravenously by cycles of 3 consecutive days (0.5 mg/kg at J1, then 1 mg/kg at J2 and J3), following the protocol for osteogenesis imperfecta. Eleven patients received from a single cycle, 1 patient received 4 cycles and 1 patient 6 cycles. Pain resistant to oral and IV NSAIDS was the main reason for all the patients. VAS was 6/10 before pamidronate, and 0/10 36 hours after pamidronate infusion for 11/13 patients. Pain persisted for 1 patient and disappeared after 3 weeks for another one. The clavicle swelling disappeared in 1/5 patients and clearly decreased in 4/5 patients. The median duration of symptom-free intervals between 2 crises was 10 months (1-21.6). Five patients had a MRI after pamidronate treatment, which showed a decrease of the number of the lesions for 4 of them. The main side effects of pamidronate infusions were mild and transient: fever (n=9) with 5 flu-like symptoms, hypocalcaemia (>2mM, n=6; 2 mM, n=5, and 2 were symptomatic). Conclusions: Our observations show that about 1/3 of patients with CRMO may present difficult to treat acute attacks of bone pain. In these cases, pamidronate appears to be the best pain relieving treatment with a rapid time of response and with limited side effects. References: Miettunen PM, Wei X, Kaura D, Reslan WA, Aguirre AN, Kellner JD. Dramatic pain relief and resolution of bone inflammation following pamidronate in 9 pediatric patients with persistent chronic recurrent multifocal osteomyelitis (CRMO). Ped Rheum J. 2009 Jan 12;7:2. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5698